Evaluation of cardioprotective effect of Aegle marmelos on doxorubicin induced cardiotoxicity: an experimental study - Vishwakarma, Pinki; Divekar, Pratik; Goel, Raj Kumar; Sharma, Monica; Saini, Manish; Saxena, K. K. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Aegle marmelos (A. marmelos), a medicinal herb, is widely used in the Indian system of medicine for treatment of various ailments. The methanolic extract of A. marmelos leaves had shown antioxidant effect. However, so far aqueous extract of A. marmelos is not scientifically evaluated for its cardio protective potential. Hence the present study was designed to find out cardio protective role of A. marmelos against doxorubicin induced cardiotoxicity. Methods: Thirty rats were randomized into five major groups (n=6). Group I received only 2ml/100g/day normal saline p.o., group II received 2ml/100g/day of normal saline p.o. followed by doxorubicin on 21st day, group III received carvedilol 30 mg/kg/day p.o., Group IV received A. marmelos 250mg/kg/day p.o. and Group V received A. marmelos 500mg/kg/day p.o. for 21days. Doxorubicin 20mg/kg i.p. single dose was given to induce cardiotoxicity in rats of group II, III, IV and V respectively on last day of experiment. Animals were sacrificed 48 hours after doxorubicin administration. Cardiac serum markers creatinine phosphokinase MB, lactate dehydrogenase, serum glutamate oxaloacetate transaminase and serum glutamate pyruvate transaminase were analysed biochemically. Histopathological changes were studied under light microscope. Results: All cardiac serum marker levels were found significantly (p<0.001) increased in doxorubicin group while A. marmelos pre-treated group displayed significant (p<0.001) reduction in rise of these parameters in a dose dependent manner indicating cardio protection. Histological observations further correlated the cardio protective effect of A. marmelos. Conclusions: The present study concluded that aqueous extract of A. marmelos possesses cardio protective potential against doxorubicin induced cardiotoxicity.